Children in Large Families: Disadvantaged or Just Different? - Gerry Redmond (Luxembourg Income Study (LIS), 2000)
In an age when there is considerable focus on the needs and rights of children, it is perhaps a little surprising that parental income still mostly determines the standard of living that children enjoy. This has important implications, not just in terms of overall levels of welfare for children, but also in terms of equity between children. This paper looks at the issue of equity between children in Western industrial societies in just one of its many dimensions: to what extent are children in large families more likely to be in poverty than children in smaller families? Aggregate and survey microdata from around 1990 are used to examine welfare state provisions and outcomes for children in families of different size in seven Western countries. The analysis finds, not surprisingly, that children in large families are more likely to be in poverty than children in small families. However, the analysis also finds that in those countries which give higher per-child family allowances to larger families, the probability of children being in poverty does not increase with family size once parents' employment status is taken into account. The paper concludes by suggesting that there is a difference between help for families and help for children that has been largely overlooked in policy debates, and a focus on policies for children is required if greater equity between children is to be realized.
Keywords: 330; Kinder; Einkommensverteilung; Lebensstandard; Familie; Haushaltseinkommen; Familienleistungsausgleich; Kanada; Australien; USA; Norwegen; Schweden; Finnland; Frankreich